VD_FINDINFO Jug / 2016 / 449 vom 28. Juni 2016 - VD Tribunal cantonal (2016)
LÉSION CORPORELLE SIMPLE, RIXE, LÉGITIME DÉFENSE, FIXATION DE LA PEINE | 123 ch. 2 al. 1 CP, 133 CP, 15 CP, 42 CP, 47 CP, 54 CP